# linear_combination' Tactic #

In this file, the `linear_combination'`

tactic is created. This tactic, which
works over `CommRing`

s, attempts to simplify the target by creating a linear combination
of a list of equalities and subtracting it from the target. A `Syntax.Tactic`

object can also be passed into the tactic, allowing the user to specify a
normalization tactic.

## Implementation Notes #

This tactic works by creating a weighted sum of the given equations with the given coefficients. Then, it subtracts the right side of the weighted sum from the left side so that the right side equals 0, and it does the same with the target. Afterwards, it sets the goal to be the equality between the lefthand side of the new goal and the lefthand side of the new weighted sum. Lastly, calls a normalization tactic on this target.

This file contains the `linear_combination'`

tactic (note the '): the original
Lean 4 implementation of the "linear combination" idea, written at the time of
the port from Lean 3. Notably, its scope includes certain *nonlinear*
operations. The `linear_combination`

tactic (in a separate file) is a variant
implementation, but this version is provided for backward-compatibility.

## References #

Result of `expandLinearCombo`

, either an equality proof or a value.

- proof: Lean.Term → Mathlib.Tactic.LinearCombination'.Expanded
A proof of

`a = b`

. - const: Lean.Term → Mathlib.Tactic.LinearCombination'.Expanded
A value, equivalently a proof of

`c = c`

.

## Instances For

Performs macro expansion of a linear combination expression,
using `+`

/`-`

/`*`

/`/`

on equations and values.

`.proof p`

means that`p`

is a syntax corresponding to a proof of an equation. For example, if`h : a = b`

then`expandLinearCombo (2 * h)`

returns`.proof (c_add_pf 2 h)`

which is a proof of`2 * a = 2 * b`

.`.const c`

means that the input expression is not an equation but a value.

Implementation of `linear_combination'`

and `linear_combination2`

.

## Equations

- One or more equations did not get rendered due to their size.

## Instances For

The `(norm := $tac)`

syntax says to use `tac`

as a normalization postprocessor for
`linear_combination'`

. The default normalizer is `ring1`

, but you can override it with `ring_nf`

to get subgoals from `linear_combination'`

or with `skip`

to disable normalization.

## Equations

- One or more equations did not get rendered due to their size.

## Instances For

The `(exp := n)`

syntax for `linear_combination'`

says to take the goal to the `n`

th power before
subtracting the given combination of hypotheses.

## Equations

- One or more equations did not get rendered due to their size.

## Instances For

`linear_combination'`

attempts to simplify the target by creating a linear combination
of a list of equalities and subtracting it from the target.
The tactic will create a linear
combination by adding the equalities together from left to right, so the order
of the input hypotheses does matter. If the `norm`

field of the
tactic is set to `skip`

, then the tactic will simply set the user up to
prove their target using the linear combination instead of normalizing the subtraction.

Note: There is also a similar tactic `linear_combination`

(no prime); this version is
provided for backward compatibility. Compared to this tactic, `linear_combination`

:

- drops the
`←`

syntax for reversing an equation, instead offering this operation using the`-`

syntax - does not support multiplication of two hypotheses (
`h1 * h2`

), division by a hypothesis (`3 / h`

), or inversion of a hypothesis (`h⁻¹`

) - produces noisy output when the user adds or subtracts a constant to a hypothesis (
`h + 3`

)

Note: The left and right sides of all the equalities should have the same
type, and the coefficients should also have this type. There must be
instances of `Mul`

and `AddGroup`

for this type.

- The input
`e`

in`linear_combination' e`

is a linear combination of proofs of equalities, given as a sum/difference of coefficients multiplied by expressions. The coefficients may be arbitrary expressions. The expressions can be arbitrary proof terms proving equalities. Most commonly they are hypothesis names`h1, h2, ...`

. `linear_combination' (norm := tac) e`

runs the "normalization tactic"`tac`

on the subgoal(s) after constructing the linear combination.- The default normalization tactic is
`ring1`

, which closes the goal or fails. - To get a subgoal in the case that it is not immediately provable, use
`ring_nf`

as the normalization tactic. - To avoid normalization entirely, use
`skip`

as the normalization tactic.

- The default normalization tactic is
`linear_combination' (exp := n) e`

will take the goal to the`n`

th power before subtracting the combination`e`

. In other words, if the goal is`t1 = t2`

,`linear_combination' (exp := n) e`

will change the goal to`(t1 - t2)^n = 0`

before proceeding as above. This feature is not supported for`linear_combination2`

.`linear_combination2 e`

is the same as`linear_combination' e`

but it produces two subgoals instead of one: rather than proving that`(a - b) - (a' - b') = 0`

where`a' = b'`

is the linear combination from`e`

and`a = b`

is the goal, it instead attempts to prove`a = a'`

and`b = b'`

. Because it does not use subtraction, this form is applicable also to semirings.- Note that a goal which is provable by
`linear_combination' e`

may not be provable by`linear_combination2 e`

; in general you may need to add a coefficient to`e`

to make both sides match, as in`linear_combination2 e + c`

. - You can also reverse equalities using
`← h`

, so for example if`h₁ : a = b`

then`2 * (← h)`

is a proof of`2 * b = 2 * a`

.

- Note that a goal which is provable by

Example Usage:

```
example (x y : ℤ) (h1 : x*y + 2*x = 1) (h2 : x = y) : x*y = -2*y + 1 := by
linear_combination' 1*h1 - 2*h2
example (x y : ℤ) (h1 : x*y + 2*x = 1) (h2 : x = y) : x*y = -2*y + 1 := by
linear_combination' h1 - 2*h2
example (x y : ℤ) (h1 : x*y + 2*x = 1) (h2 : x = y) : x*y = -2*y + 1 := by
linear_combination' (norm := ring_nf) -2*h2
/- Goal: x * y + x * 2 - 1 = 0 -/
example (x y z : ℝ) (ha : x + 2*y - z = 4) (hb : 2*x + y + z = -2)
(hc : x + 2*y + z = 2) :
-3*x - 3*y - 4*z = 2 := by
linear_combination' ha - hb - 2*hc
example (x y : ℚ) (h1 : x + y = 3) (h2 : 3*x = 7) :
x*x*y + y*x*y + 6*x = 3*x*y + 14 := by
linear_combination' x*y*h1 + 2*h2
example (x y : ℤ) (h1 : x = -3) (h2 : y = 10) : 2*x = -6 := by
linear_combination' (norm := skip) 2*h1
simp
axiom qc : ℚ
axiom hqc : qc = 2*qc
example (a b : ℚ) (h : ∀ p q : ℚ, p = q) : 3*a + qc = 3*b + 2*qc := by
linear_combination' 3 * h a b + hqc
```

## Equations

- One or more equations did not get rendered due to their size.

## Instances For

`linear_combination'`

attempts to simplify the target by creating a linear combination
of a list of equalities and subtracting it from the target.
The tactic will create a linear
combination by adding the equalities together from left to right, so the order
of the input hypotheses does matter. If the `norm`

field of the
tactic is set to `skip`

, then the tactic will simply set the user up to
prove their target using the linear combination instead of normalizing the subtraction.

Note: There is also a similar tactic `linear_combination`

(no prime); this version is
provided for backward compatibility. Compared to this tactic, `linear_combination`

:

- drops the
`←`

syntax for reversing an equation, instead offering this operation using the`-`

syntax - does not support multiplication of two hypotheses (
`h1 * h2`

), division by a hypothesis (`3 / h`

), or inversion of a hypothesis (`h⁻¹`

) - produces noisy output when the user adds or subtracts a constant to a hypothesis (
`h + 3`

)

Note: The left and right sides of all the equalities should have the same
type, and the coefficients should also have this type. There must be
instances of `Mul`

and `AddGroup`

for this type.

- The input
`e`

in`linear_combination' e`

is a linear combination of proofs of equalities, given as a sum/difference of coefficients multiplied by expressions. The coefficients may be arbitrary expressions. The expressions can be arbitrary proof terms proving equalities. Most commonly they are hypothesis names`h1, h2, ...`

. `linear_combination' (norm := tac) e`

runs the "normalization tactic"`tac`

on the subgoal(s) after constructing the linear combination.- The default normalization tactic is
`ring1`

, which closes the goal or fails. - To get a subgoal in the case that it is not immediately provable, use
`ring_nf`

as the normalization tactic. - To avoid normalization entirely, use
`skip`

as the normalization tactic.

- The default normalization tactic is
`linear_combination' (exp := n) e`

will take the goal to the`n`

th power before subtracting the combination`e`

. In other words, if the goal is`t1 = t2`

,`linear_combination' (exp := n) e`

will change the goal to`(t1 - t2)^n = 0`

before proceeding as above. This feature is not supported for`linear_combination2`

.`linear_combination2 e`

is the same as`linear_combination' e`

but it produces two subgoals instead of one: rather than proving that`(a - b) - (a' - b') = 0`

where`a' = b'`

is the linear combination from`e`

and`a = b`

is the goal, it instead attempts to prove`a = a'`

and`b = b'`

. Because it does not use subtraction, this form is applicable also to semirings.- Note that a goal which is provable by
`linear_combination' e`

may not be provable by`linear_combination2 e`

; in general you may need to add a coefficient to`e`

to make both sides match, as in`linear_combination2 e + c`

. - You can also reverse equalities using
`← h`

, so for example if`h₁ : a = b`

then`2 * (← h)`

is a proof of`2 * b = 2 * a`

.

- Note that a goal which is provable by

Example Usage:

```
example (x y : ℤ) (h1 : x*y + 2*x = 1) (h2 : x = y) : x*y = -2*y + 1 := by
linear_combination' 1*h1 - 2*h2
example (x y : ℤ) (h1 : x*y + 2*x = 1) (h2 : x = y) : x*y = -2*y + 1 := by
linear_combination' h1 - 2*h2
example (x y : ℤ) (h1 : x*y + 2*x = 1) (h2 : x = y) : x*y = -2*y + 1 := by
linear_combination' (norm := ring_nf) -2*h2
/- Goal: x * y + x * 2 - 1 = 0 -/
example (x y z : ℝ) (ha : x + 2*y - z = 4) (hb : 2*x + y + z = -2)
(hc : x + 2*y + z = 2) :
-3*x - 3*y - 4*z = 2 := by
linear_combination' ha - hb - 2*hc
example (x y : ℚ) (h1 : x + y = 3) (h2 : 3*x = 7) :
x*x*y + y*x*y + 6*x = 3*x*y + 14 := by
linear_combination' x*y*h1 + 2*h2
example (x y : ℤ) (h1 : x = -3) (h2 : y = 10) : 2*x = -6 := by
linear_combination' (norm := skip) 2*h1
simp
axiom qc : ℚ
axiom hqc : qc = 2*qc
example (a b : ℚ) (h : ∀ p q : ℚ, p = q) : 3*a + qc = 3*b + 2*qc := by
linear_combination' 3 * h a b + hqc
```

## Equations

- One or more equations did not get rendered due to their size.